Inclusions of flowers of Podopterus (Polygonaceae) in the Miocene amber of Simojovel de Allende, Chiapas, Mexico - Estrada-Ruiz, Emilio (Instituto de Ecología, A.C., 2023)
Background and Aims: The Miocene amber from Chiapas, Mexico, shows high diversity of biological inclusions such as plants, fungi, arthropods, and vertebrates, being one of the most important amber-bearing areas worldwide. The aim of this work is to describe a new record based on four bisexual flowers belonging to the fossil species Podopterus mijangosae, that has been described recently based on its winged fruits only.Methods: The morphological and anatomical characteristics of the four fossil flowers were observed using a binocular stereoscopic microscope. The taxonomic affinity was decided by consulting specialized literature, as well as the review of herbarium material of the genera Podopterus, Fallopia, and Neomillspaughia of Polygonaceae.Key results: The four fossil specimens are bisexual, small, and have actinomorphic flowers, with differentiated perianth, three petals and three sepals per series, stamens are free and with thread-like filaments, anthers are dithecal and basifixed, the ovary is superior, syncarpous, 3-angular, with three free styles, and capitate stigmas. Conclusions: This new report of flowers of Podopterus adds more evidence that the family Polygonaceae was an important component of the tropical forest of Simojovel de Allende, Chiapas, Mexico, during the Miocene.